Enhanced Production of a Plant Monoterpene by Overexpression of the 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Catalytic Domain in Saccharomyces cerevisiae - Rico, Juan (American Society for Microbiology (ASM), 2010)
Linalool production was evaluated in different Saccharomyces cerevisiae strains expressing the Clarkia breweri linalool synthase gene (LIS). The wine strain T(73) was shown to produce higher levels of linalool than conventional laboratory strains (i.e., almost three times the amount). The performance of this strain was further enhanced by manipulating the endogenous mevalonate (MVA) pathway: deregulated overexpression of the rate-limiting 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) doubled linalool production. In a haploid laboratory strain, engineering of this key step also improved linalool yield.